Implementation of the KOTAKU Program in Realizing Livable and Sustainable Urban Settlements in Banaran Village - Fadillah, Aprilia Nur; Widiyarta, Agus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The issue of slum settlements remains a strategic concern in Indonesia, including in Banaran Subdistrict, Kertosono District, Nganjuk Regency. Despite having a relatively low slum score, this area received the largest allocation of funds from the City Without Slums (KOTAKU) Program, raising questions about the effectiveness of policy implementation. This study aims to analyze the implementation of the KOTAKU Program using George C. Edwards III’s policy implementation theory, which emphasizes four aspects: communication, resources, dispose-tion, and bureaucratic structure. This research employed a descriptive qualitative approach with research subjects including village officials, the PRKPP Office, Community Self-Reliance Institutions (LKM), Community Self-Help Groups (KSM), and beneficiary communities. Data were collected through participatory observation, in-depth interviews, and documentation, with informants selected using purposive and snowball sampling techniques. The instruments used consisted of semi-structured interview guidelines and official program documents. Data analysis was conducted using Miles & Huberman’s interactive model through data reduction, data display, and conclusion drawing, with validation carried out through source, method, and time triangulation, as well as member checks. The findings show that the implementation of the KOTAKU Program in Banaran Subdistrict has been fairly effective: program communication is relatively clear and consistent, although community participation remains limited; human and informational resources are adequate, though post-construction facilities are insufficient; implementers’ disposition is highly positive and proactive; and the bureaucratic structure supports implementation with clear division of tasks, flexible SOPs, and solid coordination. In conclusion, the program has delivered tangible impacts in terms of reducing slum conditions, improving the environment, and strengthening community institutions. The study implies the importance of strengthening communication strategies, enhancing community participation, and providing post-construction facilities to ensure program sustainability.